TAYLOR SWIFT’S ALL TOO WELL TWO LIVES: A COMPARATIVE STUDY OF TAYLOR SWIFT SELF ADAPTATION ACROSS HER SONG AND SHORT FILM (Argopuro: Jurnal Ilmu Bahasa, 2025)
Taylor Swift’s All Too Well (2021) has evolved from a song into an emotionally layered short film, offering an interesting case study in self-adapted storytelling. This article aims to explore Swift’s creative agency in reinterpreting her own narrative across the two mediums, analyzing changes in thematic focus and emotional resonance. Through close textual analysis of the song’s lyrics, the short film’s visual, and narrative techniques, this analysis identifies key contrast such as the short film emphasized on nostalgia and gendered power dynamics while underscoring Swift’s consistent authorship. Findings reveal how the expansion into film allows Swift to reclaim her autobiographical narrative with broader nuance, challenging reductive interpretations of her work.